Pengendalian Jamur Ganoderma dengan Metode Perbanyakan Jamur Trichoderma pada Pembibitan Kelapa Sawit di PT PP London Sumatra Bah Lias Research Station - Utami, Mutiara Alya; Nasution, Rizki Amelia; Mawaddah, Fitri Asyiatun; Aulia, Rahma (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Ganoderma sp. generally attacks the roots or base of the tree, whether it's alive or dead. There are also other species of Ganoderma whose caps attach directly to the tree. If Ganoderma grows on wood or a tree, then it falls into the category of "lignicolous" fungi. Ganoderma sp. can cause basal stem rot (BSR) disease in oil palm or other productive plants such as rubber, coconut, and tea. The equipment used in this activity includes digital scales, beakers, measuring cups, ovens, LAF, petri dishes, needle probes, hotplates, bunsen burners, aluminum foil, autoclaves, knives, heat-resistant plastic or polypropylene, wool thread, cotton plugs, hoses, newspapers, and rubber. The materials used include potato extract, sugar, agar powder, distilled water, RWB, corn, and fine bran. 200 grams of potato extract, 10 grams of sugar, and 12 grams of agar powder are dissolved in 1000 ml of distilled water, and the rubber wood inoculum is cut into pieces measuring 6 cm x 6 cm x 6 cm and boiled for 7 hours. The experimental technique is carried out by combining the Ganoderma starter culture developed in RWB (Rubber Wood Block), then mixed with Trichoderma in its soil medium. After that, it is planted in oil palm seedlings in polybags and the percentage of oil palm seedling deaths is observed up to 12 months of age. Trichoderma, which acts as an antagonistic microbe, can suppress the growth of pathogens. By propagating Trichoderma fungi, which is one way to utilize biological agents to control 18 plant pests and diseases, it can also inhibit the percentage of deaths in oil palm seedlings. Propagating Trichoderma fungi on a nursery scale is used as a control for pests and diseases, especially Ganoderma fungi, which are currently still a pathogen in oil palm growth. By propagating Trichoderma fungi, it also cannot rule out the possibility of Ganoderma fungi growing.